2016
DOI: 10.1016/j.ophtha.2016.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study of Oral Health and Risk of Primary Open-Angle Glaucoma in Men

Abstract: Purpose Tooth loss or periodontal disease is associated with systemic endothelial dysfunction, which has been implicated in primary open-angle glaucoma (POAG). The relationship between oral health and POAG has received limited attention. Thus, we evaluated the association between oral health history and risk of POAG and POAG subtypes. Design Prospective cohort study Participants Health Professionals Follow-up Study participants (40,536 men) followed biennially from 1986 to 2012. At each 2-year risk period,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 36 publications
1
31
1
Order By: Relevance
“…We report significant correlations between an MGI of 4 and swollen joints and a family history of eye diseases. We also found a significant correlation between an MGI of 1 and optic nerve exam abnormalities, reported for the first time in an Indian population (Table 3), which is in agreement with established links between oral and opthalmologic health measured in other populations [21], [22]. We did not find significant correlations between periodontal disease and cardiovascular health.…”
Section: B Oral-systemic Health Cross Correlationssupporting
confidence: 91%
See 1 more Smart Citation
“…We report significant correlations between an MGI of 4 and swollen joints and a family history of eye diseases. We also found a significant correlation between an MGI of 1 and optic nerve exam abnormalities, reported for the first time in an Indian population (Table 3), which is in agreement with established links between oral and opthalmologic health measured in other populations [21], [22]. We did not find significant correlations between periodontal disease and cardiovascular health.…”
Section: B Oral-systemic Health Cross Correlationssupporting
confidence: 91%
“…In the same study, low BMI was significantly associated with decreased prevalence of periodontal disease among young American adults [20]. Separate studies of thousands of American adults found that recent tooth loss was significantly correlated with primary open-angle glaucoma and that periodontal disease was significantly correlated with macular degeneration in adults under the age of 60 [21], [22]. In various populations in India, periodontal disease has been found to be highly prevalent and significantly correlated with older age, coronary artery disease, tobacco use, smoking, and lower socioeconomic status [23], [24].…”
Section: Periodontal Health Epidemiologymentioning
confidence: 82%
“…Further, endothelial dysfunction is associated with impaired flow‐mediated vasodilatation, for example with effects on the blood flow to the optic nerve (Fadini et al., ; Su et al., ). While self‐reported periodontal disease was not associated, an association between self‐reported recent tooth losses with an increased risk of primary open‐angle glaucoma was shown previously (Pasquale et al., ).…”
Section: Discussionmentioning
confidence: 47%
“…Periodontitis is a chronic inflammatory condition associated with many systemic diseases (LaMonte et al, ; Pasquale et al, ), and the limitations of periodontal regeneration largely depend on the regenerative potential on the root surface (Bosshardt, ). Root cementum plays a critical role in achieving the attachment of periodontal ligament fiber to the root surface (Ripamonti, ).…”
Section: Introductionmentioning
confidence: 99%